2020
DOI: 10.1111/jep.13467
|View full text |Cite
|
Sign up to set email alerts
|

A systematic assessment on COVID‐19 preparedness and transition strategy in Bangladesh

Abstract: Rationale, aims, and objectives: The COVID-19 pandemic of 2020 has overpowered the most advanced health systems worldwide with thousands of daily deaths. The current study conducted a situation analysis on the pandemic preparedness of Bangladesh and provided recommendations on the transition to the new reality and gradual restoration of normalcy. Method: A complex adaptive system (CAS) framework was theorized based on four structural dimensions obtained from the crisis and complexity theory to help evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 35 publications
2
43
0
Order By: Relevance
“…With inept and inadequate healthcare systems, Bangladesh has been attempting to contain the impact of the COVID-19 pandemic since March 2020 [ 21 ]. Bangladesh severely lacked the preparedness to tackle the spread of COVID-19 [ 22 ], and the country’s COVID-19 testing system has also been criticized at a global level [ 5 ]. However, Bangladesh has experience of running successful immunization programs for children.…”
Section: Introductionmentioning
confidence: 99%
“…With inept and inadequate healthcare systems, Bangladesh has been attempting to contain the impact of the COVID-19 pandemic since March 2020 [ 21 ]. Bangladesh severely lacked the preparedness to tackle the spread of COVID-19 [ 22 ], and the country’s COVID-19 testing system has also been criticized at a global level [ 5 ]. However, Bangladesh has experience of running successful immunization programs for children.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Bangladesh shows that the country severely lacked the pandemic preparedness in its health and governance system. This study reported that lack of preparedness due to the “absence of planning and coordination, disproportionate resource allocations, challenged infrastructure, adherence to bureaucratic delay, lack of synchronized risk communication, failing leadership of concerned authorities, and incoherent decision-making” ( 14 ) had increased the country's epidemiologic vulnerability. However, no study was conducted to assess preparedness against the COVID-19 in Bangladesh at the individual and household levels, though research conducted elsewhere found that preparedness plays a significant role in adopting preventive practices ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, countries such as China and Bangladesh, have changed the definition of confirmed cases or recoveries during the on-going pandemic [6, 7]. Moreover, leadership and political goodwill during such crisis play a crucial role in data collection, testing quality and country-wide coverage [8].…”
Section: Rate and Quality Of Testingmentioning
confidence: 99%